Intranasal radiopacities: incidental panoramic radiograph findings - Gunduz, Kaan; Celenk, Peruze; Alkan, ALPER; ALKAN, ALPER (My University, 2010)
Nasal foreign bodies are a common source of referral to accident and emergency departments, especially in young patients. In adults, intranasal foreign bodies are rare and they result mostly from accidents, trauma, or coexisting mental disorders. Rhinoliths are mineralized, calcareous concretions that form in the nasal cavity by deposition of calcareous salts around an endogenous (e.g., teeth, bone fragments, blood clot, mucus, bacteria, or leukocytes) or exogenous (e.g., fruit seeds, beads, buttons, bits of dirt or pebbles, or remains of a gauze tampon) nucleus. This paper reports two cases of intranasal radiopacity.